Communication in organizational culture at the Balikpapan AirNav company during the COVID-19 Pandemic - Setiawan, Resdika Anggesa (Universitas Ahmad Dahlan, 2023)
Communication is an important thing to do and implement well in a company. Communication can also form a comfortable organizational culture in a company. The challenges during this pandemic require that companies survive and create a corporate culture that complies with the rules and regulations that their boss has given. The Balikpapan branch of the AirNav company experienced symptoms when many of its members were experiencing the COVID-19 virus attack at the same time. However, the company still had to be able to operate and monitor flights in Indonesia, and the performance of all company members still had to be created and maintained well even during this time. The COVID-19 pandemic is happening. This research aims to determine how communication is in the organizational culture at the AirNav Balikpapan company during the COVID-19 pandemic. The method used is a qualitative research paradigm with the nature of a case study, followed by a phenomenology and netnography approach. The results of this research are the application of rules that changed during the COVID-19 pandemic in companies and forms of communication in the organizational culture of the AirNav Balikpapan company during the pandemic by creating performance in a stable corporate culture in the company.